Improving the Resolution of Ghost Imaging via the Coefficient of Skewness - Huan Zhao; Xiaoqian Wang; Chao Gao; Zhuo Yu; Hong Wang; Yu Wang; Lidan Gou; Zhihai Yao (IEEE Photonics Journal)
Ghost imaging (GI) has been received more and more attention in past thirty years. However, it has some limitations in the resolution. In this article, we propose a scheme to improve the resolution of GI by a new imaging information, i.e. the coefficient of skewness coming from the fluctuations of the second-order correlation function, and put forward an enhanced GI protocol exploiting those fluctuations. We demonstrate experimentally that the additional information obtained from the new information makes it possible to improve resolution compared to the traditional GI scheme.